Dusty plasmas: from Saturn’s rings to semiconductor processing devices - Robert Merlino (Advances in Physics: X, 2021)
Dusty plasmas are plasmas containing solid particles in the size range of about 10 nm—10 μm. The particles acquire an electrical charge by collecting electrons and ions from the plasma, or by photo-electron emission if they are exposed to UV radiation. The charged dust particles interact with the electrons and ions, forming a multi-component plasma. Dusty plasmas occur in a number of natural environments, including planetary rings, comet tails, and solar nebulae; as well as in technological devices used to manufacture semiconductor chips, and in magnetic fusion devices. This article focuses on the physics underlying dusty plasmas, which are studied by plasma physicists, aeronomists, space physicists, and astrophysicists. The article begins with an introduction explaining what we mean by a dusty plasma, where they are found, and a summary of their basic properties. The article then presents the fundamental physics of dust charging, forces on dust particles, a description of devices used to produce dusty plasmas, strongly coupled dusty plasmas, collective phenomenon  (waves) in dusty plasmas, magnetized dusty plasmas, and the emerging technologies based on dusty plasmas. It concludes with a few perspective comments on how the field has developed historically and the prospects for future advances.